Fabrication of Piezoelectric Ceramic Hollow Fibers with Low Sintering Temperature and Their Characterization - Mensur-Alkoy, Ebru; Kaya, M. Y.; Avdan, D.; Unver, M. U.; Alkoy, S. (IEEE, 2014)
The main aim of this study is to fabricate hollow fibers using alginate gelation method and to characterize the electromechanical performance of these fibers with microtubular structure for the device applications that are based on hollow piezoceramic fibers working in d(31) mode. However, fabrication of hollow fibers is difficult and problematic. This study originally presents a holistic solution to these problems and it is different from the currently used or investigated methods in terms of method, design, composition and application. The novel points of the study are: fabrication of the hollow fibers by alginate gelation methods, investigation and use of solid solutions of lead zirconate titanate (PZT) with lead zinc niobate (PZN) with low sintering temperatures, preparation of Ag based electrodes during the processing of piezoceramic fibers and using the co-firing process due to the difficulty of obtaining the inner electrode layer.
IEEE Joint International Symposium on the Applications of Ferroelectrics / International Workshop on Acoustic Transduction Materials and Devices / Workshop on Piezoresponse Force Microscopy (ISAF/IWATMD/PFM) -- MAY 12-16, 2014 -- State College, PA
Keywords: lead-free; fiber; PZT; PZN-PZT; piezoelectrics